1987
DOI: 10.1063/1.98012
|View full text |Cite
|
Sign up to set email alerts
|

Reactively sputtered RuO2 diffusion barriers

Abstract: The thermal stability of reactively sputtered RuO2 films is investigated from the point of view of their application as diffusion barriers in silicon contact metallizations with an Al overlayer. Backscattering spectra of Si/RuO2/Al samples and electrical measurements on shallow junction diodes with 〈Si〉/TiSi2.3/RuO2/Al contacts both show that RuO2 films are effective diffusion barriers between Al and Si for 30-min annealing at temperatures as high as 600 °C.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
0

Year Published

1997
1997
2009
2009

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(34 citation statements)
references
References 4 publications
1
33
0
Order By: Relevance
“…Conductive transition metal dioxides with rutile-type structure show potential applications for substituting the metals currently used in conductive lines, which serve to connect components of semiconductor and the electrode materials in ferroelectric memory devices [2][3][4][5][6]. Osmium dioxide (OsO 2 ) belongs to the family of these compounds for which little is known on its fundamental properties.…”
Section: Introductionmentioning
confidence: 99%
“…Conductive transition metal dioxides with rutile-type structure show potential applications for substituting the metals currently used in conductive lines, which serve to connect components of semiconductor and the electrode materials in ferroelectric memory devices [2][3][4][5][6]. Osmium dioxide (OsO 2 ) belongs to the family of these compounds for which little is known on its fundamental properties.…”
Section: Introductionmentioning
confidence: 99%
“…These properties recommend RuO 2 as a non-corrosive diffusion barrier for contact metallizations in very large-scale integrated circuits (VLSI), [1,2] for film resistors, for buffer layers of high-T c superconducting films on silicon, [3] and for electrodes of ferroelectric thin films. [4] Furthermore, RuO 2 is frequently used as an electrocatalyst in chlorine production, [5] and has been proposed as a catalyst for the photodecomposition of water.…”
Section: Introductionmentioning
confidence: 99%
“…There is some question as to the reactivities of Ru, RU02, Ir and Ir02 with Si, and whether these electrodes require a diffusion barrier to prevent rapid silicide formation. For example, RU02 has been proposed as a diffusion barrier between metals such as AI and Si [112][113][114][115]. Good electrical properties have been achieved on BST deposited on patterned Ru electrodes on Si with no diffusion barrier [76,97], despite the fact that previous studies showed rapid silicide growth above 5QQ o C [81,82].…”
Section: Interaction With Simentioning
confidence: 99%